2009
DOI: 10.1002/bdra.20592
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental factors in the etiology of esophageal atresia and/or tracheoesophageal fistula: An overview of the current concepts

Abstract: Esophageal atresia and/or tracheoesophageal fistula (EA/TEF) are severe congenital anomalies. Although recent years have brought significant improvement in clinical treatment, our understanding of the etiology of these defects is lagging. Many genes and genetic pathways have been implicated in the development of EA/TEF, but only a few genes have been shown to be involved in humans, in animals, or in both. Extrapolating data from animal models to humans is not always straightforward. Environmental factors may a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 126 publications
1
39
0
2
Order By: Relevance
“…Chromosomal anomalies have been reported to occur in 6 to 10% of EA cases (Garne et al, 2007;Genevieve et al, 2007;Pedersen et al, 2012); while greater than 50% and up to two thirds of infants with EA have additional anomalies (Genevieve et al, 2007;Spitz, 2007;de Jong et al, 2010a;Pedersen et al, 2012). Given that EA is more likely to be diagnosed in conjunction with other syndromes (particularly VACTERL: Vertebral anomalies, Anal atresia, Cardiovascular anomalies, Tracheo-Esophageal fistula, Renal and/or Radial anomalies, Limb defects) or chromosomal anomalies that may result in termination of pregnancy, it is important to include terminated cases in ascertainment (Shaw-Smith, 2006;Felix et al, 2009). For some anomalies, availability and reporting of ETOPFA may increase ascertainment of cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chromosomal anomalies have been reported to occur in 6 to 10% of EA cases (Garne et al, 2007;Genevieve et al, 2007;Pedersen et al, 2012); while greater than 50% and up to two thirds of infants with EA have additional anomalies (Genevieve et al, 2007;Spitz, 2007;de Jong et al, 2010a;Pedersen et al, 2012). Given that EA is more likely to be diagnosed in conjunction with other syndromes (particularly VACTERL: Vertebral anomalies, Anal atresia, Cardiovascular anomalies, Tracheo-Esophageal fistula, Renal and/or Radial anomalies, Limb defects) or chromosomal anomalies that may result in termination of pregnancy, it is important to include terminated cases in ascertainment (Shaw-Smith, 2006;Felix et al, 2009). For some anomalies, availability and reporting of ETOPFA may increase ascertainment of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying etiology of EA has been described as multifactorial and is likely to differ across settings (Robert et al, 1993;Felix et al, 2009;de Jong et al, 2010b). In addition to maternal ethnicity and geographic location, previous studies have reported EA to be associated with maternal age (Leck et al, 1968;Harris et al, 1995), multiple gestation (Harris et al, 1995;Riley et al, 1998), infant sex (Robert et al, 1993) and use of assisted reproductive technology (Reefhuis et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, mutations/deletions affecting FOXF1, which is linked to Shh signaling, and mutation of HOXD13, a downstream target of Shh, result in a VACTERL-like phenotype (12); furthermore, several human syndromic esophageal atresias implicate deletions/mutations in genes that also seem to interact with the Shh pathway as MYCN (Feingold syndrome) (13,14), SOX2 (anophthalmia-esophageal-genital syndrome) (15,16), Mid1 (X-linked Opitz syndrome) (17,18), and Gli3 (Pallister-Hall syndrome) (19,20). These reported genetic disorders suggest that disturbances of Shh signaling due to interacting pathways may play a role in the EA-TEF/VACTERL association phenotype.…”
mentioning
confidence: 99%